Hemodialysis Patients and Nurses' Perspective: What Is a Qualified Nursing Care? - Zeinab Rohollahi; Sakineh Moghaddam Zeabadi; Seyedeh Zahra Hosseinigolafshani (Kerman University of Medical Sciences, 2022)
Background: With the high prevalence of chronic diseases such as chronic kidney disease (CKD) and consequently, the increasing number of hemodialysis (HD) patients, providing high-quality care has become a health concern in many countries. Therefore, the present study aimed to explore the concept of "qualified care" from HD patients' and nurses' points of view. Methods: This qualitative study was conducted using a content analysis approach. A total of 48 patients and nurses in the HD wards were selected through purposive and snowball sampling methods. Sampling continued until data saturation. Finally, a total of 54 interviews were conducted with the participants. The interviews were recorded with the participants' permission and analyzed using Graneheim and Lundman approach. Results: In this study, 16.7% of the nurses were male, and their mean age was 35.4 ± 7.47 years. Moreover, 50% of the HD patients were male, and their mean age was 53.1 ± 8.6 years. The results of the analysis of the interviews in response to the main question were classified into four main themes including (a) physical care, (b) psychological care, (c) ethical care, and (d) extensive skills and knowledge of the nurse. Conclusion: From the patients' and nurses' perspective, empathy and companionship in sessions, fulfilling daily needs, social support, and high-quality dialysis are the components of the concept of care. Therefore, these concepts should be considered in the care programs for HD patients designed by the healthcare team.